PENGARUH STRUKTUR GOVERNANCE DAN INTERNAL AUDIT TERHADAP FEE AUDIT EKSTERNAL PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Mohammad Al Hazmi; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the influence of the characteristics of structur governance (board commissioner and audit committee) and  intern audit on audit fees. The existence of structur governance (the board commissioner and the audit committee) and audit intern as a mechanism of checks and balances is expected to reduce control risk, so low external audit fees can be achieved.This study uses secondary data from annual reports of manufacturing companies which listed on Bursa Efek Indonesia in 2007-2011. This study uses purposive sampling method and uses multiple linear regression as the analysis instrument. Before being conducted the regression test, it is examined by using the classical assumption tests.The results of this study indicate that the independent commissioner, the meeting intensity of the board commissioner, the independency of the audit committee, the size of the audit committee, the meeting intensity of the audit committee and the expertise of the audit committee  did not influence the external audit fees. Size of the board commissioner and the intern audit have significant positive relationship on the external audit fees. It means a bigger size of the board commissioner and there is any demand about high internal control will demand a high quality audit from external auditors, resulting in higher audit fees.